2022
DOI: 10.3390/ijms232415874
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-HDP Labeling—A Non-Destructive Method for Real-Time Surveillance of the Osteogenic Differentiation Potential of hMSC during Ongoing Cell Cultures

Abstract: 99-Metastabil Technetium (99mTc) is a radiopharmaceutical widely used in skeletal scintigraphy. Recent publications show it can also be used to determine the osteogenic potential of human mesenchymal stem cells (hMSCs) by binding to hydroxyapatite formed during bone tissue engineering. This field lacks non-destructive methods to track live osteogenic differentiation of hMSCs. However, no data about the uptake kinetics of 99mTc and its effect on osteogenesis of hMSCs have been published yet. We therefore evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…This shows that PMMA does not affect the binding of 99m Tc-HDP to hydroxyapatite. This result is in line with prior studies, which showed that 99m Tc-HDP binds in a highly specific manner to hydroxyapatite [45][46][47]. Proof of this principle is fundamental for the understanding that 99m Tc-HDP uptake is directly proportional to hydroxyapatite concentrations in the probes, and consequently, is a reliable and sensitive method for accessing osteogenesis [47].…”
Section: Effects Of Pmma On the Osteogenic Potential Of Bm-hmscsupporting
confidence: 88%
See 1 more Smart Citation
“…This shows that PMMA does not affect the binding of 99m Tc-HDP to hydroxyapatite. This result is in line with prior studies, which showed that 99m Tc-HDP binds in a highly specific manner to hydroxyapatite [45][46][47]. Proof of this principle is fundamental for the understanding that 99m Tc-HDP uptake is directly proportional to hydroxyapatite concentrations in the probes, and consequently, is a reliable and sensitive method for accessing osteogenesis [47].…”
Section: Effects Of Pmma On the Osteogenic Potential Of Bm-hmscsupporting
confidence: 88%
“…The radioactive tracer 99m Technetium ( 99m Tc) bound to Hydroxydiphosphonate (HDP) directly binds to newly formed hydroxyapatite and can be quantified by an activimeter [46]. This method is a non-destructive way to measure the osteogenic potential of cells, and consequently, cell cultures remain intact for further assessment [47]. To evaluate the effects of anti-mycotic drugs on cell amounts, we performed DAPI staining and automated digital cell counts.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, it can be stated that the formation of calcium complexes took place in the osteogenically differentiated groups. As earlier studies showed, these calcium complexes are equivalent in structure to hydroxyapatite [31]. Therefore, a successful osteogenesis took place.…”
Section: Discussionmentioning
confidence: 83%
“…Here, a radioactive tracer ( 99m Tc) bound to a polyphosphate (HDP) directly binds to newly formed hydroxyapatite while this uptake can be visualized with a gamma camera and precisely quantified using an activimeter [30]. Beyond that, this is a nondestructive way to measure the amount of hydroxyapatite formed so the cell cultures remain intact for further assessment [31].…”
Section: Introductionmentioning
confidence: 99%